Creative industries & cultural science: A definitional odyssey - Potts Jason (Cultural Science)
This paper argues that the definition of cultural science depends on the definition of creative industries. The problem, however, is that unlike the definition of evolutionary economics, complexity science and new cultural studies, which are also elements of cultural science, the creative industries suffer multiple non-commensurable definitions. These are reviewed and analytic implications for the definition of cultural science are examined.